The representations of healthy eating of preschool children from an institution in Belo Horizonte - do Amaral, Larissa Lemos Gonçalves (Seven Editora, 2024)
Introduction: The development of healthy eating habits among preschool children is essential to promote improvement in quality of life in adolescence and adulthood. During the first years of life, the child builds eating habits through the experimentation of foods and the stimulation and observation of the food intake of their family members. Objective: To encourage healthy eating habits in preschool children from a civil entity in Belo Horizonte. Methods: Experience report on dynamics based on learning by modeling, using images of healthy and unhealthy foods to build a food pyramid. Positive reinforcers were used to consolidate learning. Participants were 18 children aged between two and six years, from a non-profit institution of a civil entity, of an educational and social assistance nature. The activity was developed in June 2018 during the clinical practice activities of the discipline Nursing Care for Newborn Health. There was a comparative evaluation before and after the educational action in order to measure the perception of the incorporation of knowledge, through the application of a free drawing activity with the theme: which healthy foods we should eat. After the presentation of the food pyramid and the food images, the children were invited to paste the images on the pyramid, according to the amount of food that should be consumed. Results: Most of the drawings of healthy foods made by the children after the intervention increased, as well as the choice of images that represented foods rich in nutritional value. However, it is perceived that preschool children have limitations to understand the role of nutrients and their relationship with food. Conclusion: The use of playful strategies helps the sedimentation of concepts by stimulating the children’s imagination that favors learning. DOI:https://doi.org/10.56238/sevened2024.026-050